The Influence of Leadership, Work Environment, and Employee Competence on the Performance of Employees of the UPT Puskesmas Pulau Kundur Karimun Regency Through Job Satisfaction - Azman Azman; Bambang Satriawan (Studi Akuntansi dan Bisnis Indonesia, 2025)
Purpose: The purpose of the research is to determine the influence of leadership, work environment, competence and job satisfaction on performance. Methodology/approach: A quantitative research design was applied using survey data from 205 respondents. Data analysis employed the SmartPLS application to test validity, reliability, and structural equation modeling, assessing both direct and mediated relationships among variables. Results/findings: Leadership, work environment, and competence have a significant positive effect on job satisfaction and performance, with job satisfaction acting as a mediator; the model explains 90% of performance variation. Conclusions: Effective leadership, good work environment, and strong competence boost job satisfaction, which improves performance. Limitations: The study focuses on one public health center, limiting generalizability. Self-reported data may be subject to bias, and the cross-sectional design restricts causal inference. Contribution: Provides evidence that leadership, work environment, and competence improve performance through job satisfaction in public health services.